ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA SMK AGRIBISNIS DALAM KONTEKS BUDIDAYA IKAN LELE - Febriani Rahayu; Ai Tusi Fatimah; Nur Eva Zakiah (Faculty of Teacher Training and Education, 2026)
ABSTRACTBased on the results of PISA, it shows that mathematics in Indonesia is still relatively low in its reasoning ability. Mathematical reasoning ability is also included in the objectives of mathematics learning. The purpose of this study is to analyze the mathematical reasoning ability of SMKN 1 Cipaku students, more precisely in the Freshwater Fisheries Agribusiness expertise in the context of catfish cultivation. This study uses a qualitative approach with a case study strategy. The subjects used were 15 people who were class XI Agribusiness students at one of the SMK in Ciamis. Data collection techniques used in this study were mathematical reasoning ability test sheets, interviews and documentation. Data analysis was carried out by applying the data analysis model from Miles, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that: (1) The mathematical reasoning ability of SMK Agribusiness students in the context of catfish cultivation is quite good. Students' reasoning ability is very strong in the flexibility indicator and the ability to use mathematical concepts or rules. Indicators of novelty have been seen in some students, but not all. While the reasonableness indicator still needs to be developed further in most students (2) The solutions produced by students are still not clear and reasonable. This shows that the novelty indicator is only visible in some students and the reasonableness indicator is still relatively low or less visible in most.